On the Translation of Polybius 1.1.2 - Parmeggiani, Giovanni (Histos, 2014)
This paper deals with the meaning of the words πάντες ὡς ἔπος εἰπεῖν ἀρχῇ καὶ τέλει κέχρηνται τούτῳ in the proem to Polybius’ Histories (1.1.2). Unlike previous translations, the reading should be: ‘all of them [sc. the previous historians], from beginning to end, so to speak, made use of it [sc. praised history]’. In particular, ἀρχῇ καὶ τέλει should be linked to πάντες, and, together with it, referred to the insistence with which previous historians addressed the praise of history in their historical narratives, and to the community of earlier historians at whom Polybius looks back, albeit in a cursory way.